Life-extending control of mechanical structures: Experimental verification of the concept - Tangirala, S.; Holmes, M.; Ray, A.; Carpino, M. (Automatica (Oxford), 1998)
The concept of life-extending control is built upon the two disciplines of Systems Science and Mechanics of Materials, and its goal is to achieve an optimized trade-off between dynamic performance and structural durability of the plant under control. Experimental and simulation results reported in recent publications show that a life extending control system can substantially reduce the structural damage accumulated in critical components with no significant loss of plant performance. This enhancement of structural durability is accomplished via nonlinear optimization to generate a sequence of open-loop commands that maneuver the plant from a known initial state, along a prescribed trajectory, close to the final desired-state subject to constraints on the damage rate and accumulation in critical components. This paper presents a methodology for analytical development of a robust feedforward-feedback control policy for life extension and high performance of mechanical structures. The concept of life-extending control is experimentally verified in a laboratory testbed which is a two-degree-of-freedom (2DOF) mechanical system excited by a computer-controlled shaker table. Test results demonstrate that the fatigue life of test specimens can be substantially extended with no appreciable degradation in the dynamic performance of the mechanical system.